Incomplete viral suppression and mortality in HIV patients after antiretroviral therapy initiation. (10th September 2017) - Lee, Jennifer S.; Cole, Stephen R.; Richardson, David B.; Dittmer, Dirk P.; Miller, William C.; Moore, Richard D.; Kitahata, Mari; Mathews, Christopher; Mayer, Kenneth; Geng, Elvin; Achenbach, Chad J.; Eron, Joseph J.
Abstract : Objective: To determine whether there is a threshold of detectable HIV RNA under 1000 copies/ml after antiretroviral therapy initiation associated with 10-year all-cause mortality. Design: This study included nearly 8000 patients from a US-based multicenter clinical cohort who started antiretroviral therapy between 1 January 1998 and 31 December 2013. Viral load was assessed 6 months after initiation of therapy. Patients were followed from 6 months after therapy initiation (between 1 July 1998 and 30 June 2014) until death, and data were administratively censored after 10 years or on 31 December 2014. Methods: We used nonparametric multiple imputation to account for left-censored viral load measurements, Cox proportional hazards models to estimate all-cause mortality hazard ratios, Nelson–Aalen cumulative hazard estimates to construct risk curves, and inverse probability of exposure weights to standardize estimated hazard ratios and risk curves to the total study population. Results: Plots of standardized hazard ratio estimates and 95% confidence intervals indicated there was no demonstrable viral load threshold between 30 and 500 copies/ml associated with a marked increase in 10-year mortality. The standardized 10-year risk of mortality among patients with viral loads between 400 and 999 copies/ml 6 months after starting treatment was comparable with the risk of mortality among patients with viral loads between 1000 and 4 million copies/ml (20 vs. 23%). Conclusion: Incomplete suppression of plasma HIV RNA 6 months after starting therapy is associated with substantial 10-year all-cause mortality risk, highlighting the importance of rapid viral load suppression after therapy initiation. Abstract : Supplemental Digital Content is available in the text